The know-how of face transplantation - Siemionow, Maria Z.; SpringerLink (Online service). (London New York Springer, 2011)
The book is laid out in 6 sections: 1. Preclinical Approaches to Face Transplantation 2. Clinical Aspects in Preparation to Face Transplantation in Humans 3. Approval Process of Face Transplantation in Humans 4. Social and Public Relations in Face Transplantation 5. World Experience with Face Transplantation in Humans 6. Future Directions in Face Transplantation This book spans the entire process of a face transplantation, from detailing the anatomy of the face to considering the social and ethical challenges of the procedure. This rigorous presentation of face transplantation also includes the anesthesia involved, the role of Institutional Review Boards in approving the operation, the financial aspects and media response. Since the authorship is international, the book considers the different perspectives, approaches and responses from across the world.
Section I: Preclinical approaches to face transplantation -- Face as an organ - the functional anatomy of the face -- Immunological aspects of face transplantation (face as CTA, immunosuppression, protocols) -- Experimental studies in face transplantation (rodents, swine,primate models) -- Cadaver studies in face transplantation (mock transplants, identity transplants) -- Section II: Clinical aspects in preparation to face transplantation in humans -- Technical aspects of face transplantation -- Anesthesia and intensive care in face transplantation -- Alternative approaches to face transplantation -- Multidisciplinary approach to face transplantation -- Ethical aspects of face transplantation -- Psychological aspects of face transplanation -- Rehabilitation and physical therapy aspects of face transplantation -- Section III: Approval process of face transplantation in humans -- Institutional review boards approval process -- Informed consent approval process -- Legal aspects of organ and tissue donation - the worldwide differences -- The issue of death and end of life -- Organ procurement organization and approval process -- Section IV: Social and public relations in face transplantation -- Philosophical view on face and face transplantation -- Social aspects of face transplantation -- Financial aspects of face transplantation -- Media related aspects of face transplantation -- Section V: World experience with face transplantation in humans -- French experience with face transplantation -- Chinese experience with face transplantation -- US experience with face transplantation -- British experience with face transplantation -- Section VI: Future directions in face transplantation -- International registry of face transplantation -- Transplantation of functional subunits of face including nose, lips, eyelids, ears and scalp transplantation -- Addressing cultural, religious and philosopical differences in addressing face transplantation -- Computerized modeling and face transplantation -- Tissue engineering and face transplantation -- New immunosuppresive strategies in face transplantation.
Electronic reproduction.
Keywords: Face -- Transplantation; Surgery, Plastic; Electronic books